2002
DOI: 10.1029/2001ja000187
|View full text |Cite
|
Sign up to set email alerts
|

Radiation belt electron flux dropouts: Local time, radial, and particle‐energy dependence

Abstract: [1] The radiation belt electrons in Earth's magnetosphere exhibit substantial variability driven by changing solar wind conditions. The electron dynamics are due to a number of different adiabatic and nonadiabatic processes that can result in rapid increases and decreases in the particle flux levels. In this paper we present observations of abrupt flux decreases driven by a moderate geomagnetic storm. The particle dynamics are found to have significant local time and energy dependence that developed over rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 26 publications
10
161
2
Order By: Relevance
“…This can be seen most clearly in the 2.5-3.2 MeV differential channel (Figures 1e and 1f ). Flux decreases during the main phase are well known and are often attributed to both actual loss and charged particle response to changing magnetic field (under the assumption of adiabatic invariance, particularly the first invariant), i.e., the so-called Dst effect [Li et al, 1997;Kim and Chan, 1997;Onsager et al, 2002]. However, unlike the >2 MeV electrons measured by REPT, these ⪆400 keV electrons measured by MagEIS increase at an earlier time, responding to the high-speed solar wind stream.…”
Section: Energetic Electron Observationsmentioning
confidence: 71%
See 1 more Smart Citation
“…This can be seen most clearly in the 2.5-3.2 MeV differential channel (Figures 1e and 1f ). Flux decreases during the main phase are well known and are often attributed to both actual loss and charged particle response to changing magnetic field (under the assumption of adiabatic invariance, particularly the first invariant), i.e., the so-called Dst effect [Li et al, 1997;Kim and Chan, 1997;Onsager et al, 2002]. However, unlike the >2 MeV electrons measured by REPT, these ⪆400 keV electrons measured by MagEIS increase at an earlier time, responding to the high-speed solar wind stream.…”
Section: Energetic Electron Observationsmentioning
confidence: 71%
“…However, an interesting and unusual aspect is the lack of significant and substantial flux decreases in the main phase of the moderate geomagnetic storm associated with the passage of the HSS. The higher-energy differential channel electrons measured by REPT, shown in Figure 1, do show a decrease in the main phase most clearly evident in the 2.5-3.2 MeV channel, suggesting that this decrease is mostly adiabatic rearrangement, i.e., the Dst effect [Li et al, 1997;Kim and Chan, 1997;Onsager et al, 2002] and not an actual loss, since the lower energy electrons decrease only slightly.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies have indicated that the largest flux variations occur during geomagnetic storms (Baker et al 1994;Li et al 1997). Typically, relativistic electron fluxes decrease during the geomagnetic storm main phase and recover during the storm recovery phase (Baker et al 1994;Onsager et al 2002;Horne et al 2009). Intense relativistic electron flux variations have also been noted during high-speed solar wind streams (HSSs) (Paulikas and Blake 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Onsager et al (2002) showed an example of radiation belt electron flux dropout that manifested over all local times (as seen at geosynchronous orbit for more than 2 MeV electrons) over about 10 h, though local dropouts occurred more rapidly with time scales of less than 4 h. A statistical analysis of rapid dropouts of relativistic electron flux at geostationary orbit by Green et al (2004) showed localized depletions in more than 2 MeV electron flux occurring over 1-2 h, spreading to all local times by 8 h after the start of the dropout. Bortnik et al (2006) have analysed a radiation belt dropout that showed a rapid, non-adiabatic loss of relativistic electrons from a range of L-shells.…”
Section: Introduction (A) the Outer Electron Radiation Beltmentioning
confidence: 99%